2007
DOI: 10.1186/1471-2296-8-23
|View full text |Cite
|
Sign up to set email alerts
|

Practice development plans to improve the primary care management of acute asthma: randomised controlled trial

Abstract: Background: Our professional development plan aimed to improve the primary care management of acute asthma, which is known to be suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…These links can be for direct advice on patient care but are also useful to discuss case studies in the abstract that may help a given practitioner with clinical decision‐making in the future. As a technique it was reported in three studies 35,50,51 . All three studies reported significant changes in knowledge or practice or outcomes.…”
Section: Resultsmentioning
confidence: 98%
“…These links can be for direct advice on patient care but are also useful to discuss case studies in the abstract that may help a given practitioner with clinical decision‐making in the future. As a technique it was reported in three studies 35,50,51 . All three studies reported significant changes in knowledge or practice or outcomes.…”
Section: Resultsmentioning
confidence: 98%
“…This, however, may be a consequence of the databases used in our search. Nonetheless, within the health-related trials, an extremely broad selection of research domains can be observed, including, for example, HIV [42], asthma [43], hand hygiene [44], prostate cancer [45] and water contamination [46]. Moreover these trials have been conducted in a wide array of countries across Europe, North and South America, Asia and Africa, with the UK and USA accounting for the most, 20 studies each.…”
Section: Resultsmentioning
confidence: 99%
“…It is recognised that simple dissemination of information is insufficient, and more complex initiatives are required to effect change. 8 The range of backgrounds of our respondents suggests a need for accessible forms of information extending across traditional professional boundaries.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 98%